2017
DOI: 10.1002/bit.26400
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Lactococcus lactis for efficient conversion of cellodextrins into L‐lactic acid

Abstract: Lactic acid bacteria (LAB) are among the most interesting organisms for industrial processes with a long history of application as food starters and biocontrol agents, and an underexploited potential for biorefineries converting biomass into high-value compounds. Lactic acid (LA), their main fermentation product, is among the most requested chemicals owing to its broad range of applications. Notably, LA polymers, that is, polylactides, have high potential as biodegradable substitutes of fossil-derived plastics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…lactis IL1403, i.e. one of the very reference LAB strains, has shown the natural ability to ferment up to cellotetraose/cellopentaose (Gandini et al 2017). This study has indicated that this strain is equipped with membrane transporters for short cellodextrins, although they have not been identified yet.…”
Section: Lab Ability To Ferment Soluble Mono-/oligo-saccharides From Lignocellulosic Biomassmentioning
confidence: 92%
See 1 more Smart Citation
“…lactis IL1403, i.e. one of the very reference LAB strains, has shown the natural ability to ferment up to cellotetraose/cellopentaose (Gandini et al 2017). This study has indicated that this strain is equipped with membrane transporters for short cellodextrins, although they have not been identified yet.…”
Section: Lab Ability To Ferment Soluble Mono-/oligo-saccharides From Lignocellulosic Biomassmentioning
confidence: 92%
“…Forefront research in development of 2 nd generation biorefinery includes endowing microorganisms that produce high-value chemicals with the ability to directly ferment lignocellulose without prior physico-chemical and/or enzymatic pre-treatment through recombinant techniques (Mazzoli et al 2012). The number of examples of recombinant cellulolytic strategies (RCS) addressed to LAB is growing (Mazzoli et al 2014;Gandini et al 2017;Stern et al 2018).…”
Section: Construction Of Recombinant Cellulolytic/hemicellulolytic Lab Through Metabolic Engineeringmentioning
confidence: 99%
“…Development of such CBP could significantly reduce the current cost of LA. Most previous metabolic engineering strategies aimed at direct fermentation of lignocellulose to LA have attempted to introduce (hemi)cellulolytic characteristics in natural producers of LA [30,31]. The approach used in the present study focused on improving the expression of the native LDH of the cellulolytic bacterium C. thermocellum DSM1313 by functionally replacing its native promoter with stronger ones.…”
Section: Discussionmentioning
confidence: 99%
“…A L. lactis strain that secreted endoglucanase and β ‐glucosidase was developed through the construction of an artificial operon. This strain was able to metabolize cellooctaose to L ‐LA .…”
Section: Promising Solutionsmentioning
confidence: 99%